COVID-19, mobility restriction, and sexual behavior among a cohort of people of reproductive age: Nigeria - Adekola, Paul O.; Ugwu, Favour C.; Amoo, Emmanuel O.; Olawole-Isaac, Adebanke; Cirella, Giuseppe T. (Frontiers in Public Health, 2023)
Background One of the non-pharmaceutical strategies adopted by various governments to control the spread of COVID-19 is mobility restriction (MR), popularly known as a lockdown. Evidence shows that MR has some unintended consequences, such as increased cases of domestic violence, rape, pornography, sex chats, incest, and other unhealthy sexual behaviors (SBs). Methods The study examined the influence of MR on SB in Owerri via a cross-sectional quantitative approach. A total of 425 interviewees were randomly chosen among people of a reproductive age. Data were analyzed using univariate, bivariate, and multivariate levels of analysis. Results A significant relationship exists between selected socio-demographic characteristics, such as age and marital status, and the ability of people to cope with sexual abstinence. Results from the logistic regression analysis further illustrated this observation as during MR people were twice as likely to engage in prolific sex chats that could spur other harmful SBs. Conclusion It is recommended that people should be allowed to determine whether they would like to stay with their partners in subsequent lockdowns, or otherwise, to prevent some of the unpleasant SBs recorded.